Difference between revisions of "009A Sample Final 1, Problem 2"

From Math Wiki
Jump to navigation Jump to search
 
(2 intermediate revisions by the same user not shown)
Line 1: Line 1:
 
<span class="exam"> Consider the following piecewise defined function:
 
<span class="exam"> Consider the following piecewise defined function:
  
::::::<math>f(x) = \left\{
+
::<math>f(x) = \left\{
 
     \begin{array}{lr}
 
     \begin{array}{lr}
 
       x+5 &  \text{if }x < 3\\
 
       x+5 &  \text{if }x < 3\\
Line 8: Line 8:
 
   \right.
 
   \right.
 
</math>
 
</math>
::<span class="exam">a) Show that <math style="vertical-align: -5px">f(x)</math> is continuous at <math style="vertical-align: 0px">x=3.</math>
+
<span class="exam">(a) Show that &nbsp;<math style="vertical-align: -5px">f(x)</math>&nbsp; is continuous at &nbsp;<math style="vertical-align: 0px">x=3.</math>
  
::<span class="exam">b) Using the limit definition of the derivative, and computing the limits from both sides, show that <math style="vertical-align: -3px">f(x)</math> is differentiable at <math style="vertical-align: 0px">x=3.</math>
+
<span class="exam">(b) Using the limit definition of the derivative, and computing the limits from both sides, show that &nbsp;<math style="vertical-align: -3px">f(x)</math>&nbsp; is differentiable at &nbsp;<math style="vertical-align: 0px">x=3</math>.
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Foundations: &nbsp;  
 
!Foundations: &nbsp;  
 
|-
 
|-
|Recall:
+
|'''1.''' &nbsp;<math style="vertical-align: -5px">f(x)</math>&nbsp; is continuous at &nbsp;<math style="vertical-align: 0px">x=a</math>&nbsp; if
 
|-
 
|-
|'''1.''' <math style="vertical-align: -5px">f(x)</math>&thinsp; is continuous at <math style="vertical-align: 0px">x=a</math>&thinsp; if <math style="vertical-align: -14px">\lim_{x\rightarrow a^+}f(x)=\lim_{x\rightarrow a^-}f(x)=f(a).</math>
+
|&nbsp; &nbsp; &nbsp; &nbsp;<math style="vertical-align: -14px">\lim_{x\rightarrow a^+}f(x)=\lim_{x\rightarrow a^-}f(x)=f(a).</math>
 
|-
 
|-
|'''2.''' The definition of derivative for <math style="vertical-align: -5px">f(x)</math>&thinsp; is &thinsp;<math style="vertical-align: -13px">f'(x)=\lim_{h\rightarrow 0}\frac{f(x+h)-f(x)}{h}.</math>
+
|'''2.''' The definition of derivative for &nbsp;<math style="vertical-align: -5px">f(x)</math>&nbsp; is  
 +
|-
 +
|&nbsp; &nbsp; &nbsp; &nbsp;<math style="vertical-align: -13px">f'(x)=\lim_{h\rightarrow 0}\frac{f(x+h)-f(x)}{h}.</math>
 
|}
 
|}
 +
  
 
'''Solution:'''
 
'''Solution:'''
Line 29: Line 32:
 
!Step 1: &nbsp;  
 
!Step 1: &nbsp;  
 
|-
 
|-
|We first calculate <math style="vertical-align: -14px">\lim_{x\rightarrow 3^+}f(x).</math> We have
+
|We first calculate &nbsp;<math style="vertical-align: -14px">\lim_{x\rightarrow 3^+}f(x).</math>&nbsp; We have
 
|-
 
|-
 
|
 
|
::<math>\begin{array}{rcl}
+
&nbsp; &nbsp; &nbsp; &nbsp;<math>\begin{array}{rcl}
 
\displaystyle{\lim_{x\rightarrow 3^+}f(x)} & = & \displaystyle{\lim_{x\rightarrow 3^+} 4\sqrt{x+1}}\\
 
\displaystyle{\lim_{x\rightarrow 3^+}f(x)} & = & \displaystyle{\lim_{x\rightarrow 3^+} 4\sqrt{x+1}}\\
 
&&\\
 
&&\\
Line 44: Line 47:
 
!Step 2: &nbsp;
 
!Step 2: &nbsp;
 
|-
 
|-
|Now, we calculate <math style="vertical-align: -14px">\lim_{x\rightarrow 3^-}f(x).</math> We have
+
|Now, we calculate &nbsp;<math style="vertical-align: -14px">\lim_{x\rightarrow 3^-}f(x).</math>&nbsp; We have
 
|-
 
|-
 
|
 
|
::<math>\begin{array}{rcl}
+
&nbsp; &nbsp; &nbsp; &nbsp;<math>\begin{array}{rcl}
 
\displaystyle{\lim_{x\rightarrow 3^-}f(x)} & = & \displaystyle{\lim_{x\rightarrow 3^-} x+5}\\
 
\displaystyle{\lim_{x\rightarrow 3^-}f(x)} & = & \displaystyle{\lim_{x\rightarrow 3^-} x+5}\\
 
&&\\
 
&&\\
Line 59: Line 62:
 
!Step 3: &nbsp;
 
!Step 3: &nbsp;
 
|-
 
|-
|Now, we calculate <math style="vertical-align: -5px">f(3).</math> We have
+
|Now, we calculate &nbsp;<math style="vertical-align: -5px">f(3).</math>&nbsp; We have
 
|-
 
|-
 
|
 
|
::<math>f(3)=4\sqrt{3+1}\,=\,8.</math>
+
&nbsp; &nbsp; &nbsp; &nbsp;<math>f(3)=4\sqrt{3+1}\,=\,8.</math>
 +
|-
 +
|Since
 
|-
 
|-
|Since <math style="vertical-align: -15px">\lim_{x\rightarrow 3^+}f(x)=\lim_{x\rightarrow 3^-}f(x)=f(3),~f(x)</math>&thinsp; is continuous.
+
|&nbsp; &nbsp; &nbsp; &nbsp; <math style="vertical-align: -15px">\lim_{x\rightarrow 3^+}f(x)=\lim_{x\rightarrow 3^-}f(x)=f(3),</math>
 +
|-
 +
|<math style="vertical-align: -5px">f(x)</math>&nbsp; is continuous at &nbsp;<math style="vertical-align: 0px">x=3.</math>
 
|}
 
|}
  
Line 72: Line 79:
 
!Step 1: &nbsp;  
 
!Step 1: &nbsp;  
 
|-
 
|-
|We need to use the limit definition of derivative and calculate the limit from both sides.  
+
|We need to use the limit definition of derivative and calculate the limit from both sides. So, we have
|-
 
|So, we have
 
 
|-
 
|-
 
|
 
|
::<math>\begin{array}{rcl}
+
&nbsp; &nbsp; &nbsp; &nbsp;<math>\begin{array}{rcl}
 
\displaystyle{\lim_{h\rightarrow 0^-}\frac{f(3+h)-f(3)}{h}} & = & \displaystyle{\lim_{h\rightarrow 0^-}\frac{(3+h)+5-8}{h}}\\
 
\displaystyle{\lim_{h\rightarrow 0^-}\frac{f(3+h)-f(3)}{h}} & = & \displaystyle{\lim_{h\rightarrow 0^-}\frac{(3+h)+5-8}{h}}\\
 
&&\\
 
&&\\
Line 94: Line 99:
 
|-
 
|-
 
|
 
|
::<math>\begin{array}{rcl}
+
&nbsp; &nbsp; &nbsp; &nbsp;<math>\begin{array}{rcl}
 
\displaystyle{\lim_{h\rightarrow 0^+}\frac{f(3+h)-f(3)}{h}} & = & \displaystyle{\lim_{h\rightarrow 0^+}\frac{4\sqrt{3+h+1}-8}{h}}\\
 
\displaystyle{\lim_{h\rightarrow 0^+}\frac{f(3+h)-f(3)}{h}} & = & \displaystyle{\lim_{h\rightarrow 0^+}\frac{4\sqrt{3+h+1}-8}{h}}\\
 
&&\\
 
&&\\
Line 116: Line 121:
 
!Step 3: &nbsp;
 
!Step 3: &nbsp;
 
|-
 
|-
|Since <math style="vertical-align: -14px">\lim_{h\rightarrow 0^-}\frac{f(3+h)-f(3)}{h}=\lim_{h\rightarrow 0^+}\frac{f(3+h)-f(3)}{h},</math>
+
|Since  
 
|-
 
|-
|<math style="vertical-align: -5px">f(x)</math>&thinsp; is differentiable at <math style="vertical-align: 0px">x=3.</math>
+
|&nbsp; &nbsp; &nbsp; &nbsp;<math style="vertical-align: -14px">\lim_{h\rightarrow 0^-}\frac{f(3+h)-f(3)}{h}=\lim_{h\rightarrow 0^+}\frac{f(3+h)-f(3)}{h},</math>
 +
|-
 +
|<math style="vertical-align: -5px">f(x)</math>&nbsp; is differentiable at &nbsp;<math style="vertical-align: 0px">x=3.</math>
 
|}
 
|}
 +
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Final Answer: &nbsp;  
 
!Final Answer: &nbsp;  
 
|-
 
|-
|'''(a)''' Since <math style="vertical-align: -14px">\lim_{x\rightarrow 3^+}f(x)=\lim_{x\rightarrow 3^-}f(x)=f(3),~f(x)</math>&thinsp; is continuous.
+
|&nbsp; &nbsp; '''(a)''' &nbsp; &nbsp; Since <math style="vertical-align: -14px">\lim_{x\rightarrow 3^+}f(x)=\lim_{x\rightarrow 3^-}f(x)=f(3),~f(x)</math>&thinsp; is continuous at <math style="vertical-align: 0px">x=3.</math>
 
|-
 
|-
|'''(b)''' Since <math style="vertical-align: -14px">\lim_{h\rightarrow 0^-}\frac{f(3+h)-f(3)}{h}=\lim_{h\rightarrow 0^+}\frac{f(3+h)-f(3)}{h},</math>  
+
|&nbsp; &nbsp; '''(b)''' &nbsp; &nbsp; Since <math style="vertical-align: -14px">\lim_{h\rightarrow 0^-}\frac{f(3+h)-f(3)}{h}=\lim_{h\rightarrow 0^+}\frac{f(3+h)-f(3)}{h},</math>  
 
|-
 
|-
 
|
 
|
::<math style="vertical-align: -5px">f(x)</math>&thinsp; is differentiable at <math style="vertical-align: 0px">x=3.</math>
+
&nbsp; &nbsp; &nbsp; &nbsp; &nbsp; &nbsp; &nbsp; <math style="vertical-align: -5px">f(x)</math>&thinsp; is differentiable at <math style="vertical-align: 0px">x=3.</math>
 
|}
 
|}
 
[[009A_Sample_Final_1|'''<u>Return to Sample Exam</u>''']]
 
[[009A_Sample_Final_1|'''<u>Return to Sample Exam</u>''']]

Latest revision as of 08:07, 10 April 2017

Consider the following piecewise defined function:

(a) Show that    is continuous at  

(b) Using the limit definition of the derivative, and computing the limits from both sides, show that    is differentiable at  .

Foundations:  
1.    is continuous at    if
       
2. The definition of derivative for    is
       


Solution:

(a)

Step 1:  
We first calculate    We have

       

Step 2:  
Now, we calculate    We have

       

Step 3:  
Now, we calculate    We have

       

Since
       
  is continuous at  

(b)

Step 1:  
We need to use the limit definition of derivative and calculate the limit from both sides. So, we have

       

Step 2:  
Now, we have

       

Step 3:  
Since
       
  is differentiable at  


Final Answer:  
    (a)     Since   is continuous at
    (b)     Since

                is differentiable at

Return to Sample Exam